Professional development: a study of secondary teachers' experiences and perspectives. - Scott, Shelleyann (Curtin University, 2002)
This research was undertaken to explore professional development in Western Australia secondary schools from the perspective of the classroom teacher. A study that bridged quantitative and qualitative methodology, it drew upon teachers' perspectives and reports of professional development activities in which they had been involved over an eighteen month period.The major focuses of the study were in exploring teachers' perceptions of their professional development activities across the following dimensions: choice, the influence of career stage, rationale for choice, equity in relation to access, levels of participation, gender factors, perceptions of effectiveness, influence of school/educational culture.The conceptual framework in this study (refer to Figure 2.1) acknowledges the teacher as the central point of reference due to his/her importance in the classroom as the architect of the learning experiences for students (Fogarty, 1999. Four aspects were identified as influences on teachers. These were professional development; factors affecting teachers' capacity to develop professionally; technological change in education; and the education system in which teachers work. Literature related to these four aspects was explored.The findings of this study, based upon in-depth interviews with teachers, indicated that the respondents were expending significant amounts of time engaged in professional development. Results demonstrated that half of the reported hours (150 hours/person/year) involved personally selected professional development. Teachers' rationale for choosing professional development was in order to become a more effective practitioner resulting in increased learning opportunities for their students. Effectiveness of professional development was predominantly related to the relevancy to teaching, level of interaction within the session, opportunities to obtain and discuss teaching materials, and the opportunities for reflection on their practices with colleagues.Career stage did indeed appear to influence teachers' choice of professional development, perceptions of effectiveness and quality, personal teaching philosophies, and perceptions of the school and educational culture. Less experienced teachers and those in the final career stage were more focused on increasing their repertoire of teaching strategies. Experienced teachers in the middle career stages were largely concerned with increasing subject knowledge, and expertise required to assist them in their additional duties other than teaching.Equity in accessing professional development was a distinct issue for rural teachers information technology teachers in this study. Information technology teachers reported experiencing frustration with the expense involved, and difficulties in accessing targeted professional development that catered to their specific requirements. Teachers situated in rural areas expressed concern with the lack of choice available to them in the rural situation. This was largely due to extensive travel time to the metropolitan area to attend specific programs, expense involved in accessing professional development and the lack of support by administration in their schools related to professional development.The teachers in this study displayed gender differences in relation to their perceptions and choices of professional development. Female teachers were generally more focused on professional development that directly related to their teaching whereas their male counterparts were overtly seeking professional development that would advance their career aspirations. Family commitments were more frequently cited by male respondents as the reason for non-attendance at out-of-hours professional development.School culture was acknowledged by teachers in this study as having an impact on professional development. Teachers resoundingly indicated they desired more self-determination in decision-making related to professional development. They expressed the perspective that the employer was demonstrating a lack of trust in teachers' professionalism and was not providing professional development to meet their teaching needs. It appeared that the professional development being provided was ad hoc and a more systematic approach was needed.As a result of this research a model of systematic professional development has been proposed that encompasses the expressed needs of teachers in this study, the literature on effective professional development to improve student learning, and the quality assurance and accountability mechanisms required by the employer.